Addressing the Letter : Italian Women Writers' Epistolary - Salsini, Laura A. (Laura Anne) (Book collections on Project MUSE., 2010)
"Women writers of nineteenth- and twentieth-century Italy reinvigorated the modern epistolary novel through their re-fashioning of the genre as a tool for examining women's roles and experiences. Addressing the Letter argues that many epistolary novels purposely tie narrative structure to thematic content, creating in the process powerful texts that reflect and challenge literary and socio-cultural norms. Through the lens of the genre, Laura A. Salsini considers how the works of authors including the Marchesa Colombi, Sibilla Aleramo, Gianna Manzini, Natalia Ginzburg, and Oriana Fallaci highlight such issues as love, the loss of ideals, lack of communication and connection, and feminist ideology. She also analyses what may be the first woman-authored Italian example of epistolary fiction: Orintia Romagnuoli Sacrati's Lettere di Giulia Willet (1818). In their reworking of the epistolary narrative form, Italian women writers challenged dominant assumptions about female behaviours, roles, relationships, and sexuality in modern Italy"--Publisher description.